PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MEDIA ULTISOLYANG DIBERI BERBAGAIKOMBINASI PUPUK KOMPOSTANDAN KOSONG KELAPA SAWIT (TKKS) DENGAN PUPUK NPK. - Roni Jerri Sijabat; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed to get the best treatment of combinationoil palm empty fruit bunches(OPEFB)compost with NPK fertilizer for the growth of oil palm seedlings (Elaeis guineensis Jacq.)inUltisol medium. This research has been conducted in the Agriculture Experimental Station Faculty of Agriculture, University of Riau, District of Tampan, the research was carried out for 4 months starting in November 2016 to the month ofFebruary2017.This research arranged experimentaly using Completely Randomized Design (CRD) arranged in non-factorial, which consist of 5 treatment and 4 replication,Every experimental unit consisted of 2 polybags so that entirely 40experimental units. P0: Without fertilizer, P1:OPEFBcompost50 g/10 kg medium + NPK 10 g/10 kg medium. P2:OPEFBcompost50 g/10 kg medium + NPK 20 g/10 kg medium. P3:OPEFBcompost100 g/10 kg medium + NPK 10 g/10 kg medium. P4: OPEFBcompost50 g/10 kg medium + NPK 20 g/10 kg medium. Analysis of variance result showing significant difference, continued with Duncans New Multiple Range Test (DNMRT) at level 5%. Based on research result which has been done indicates that giving various doses of combinations OPEFBcompost with NPK fertilizer give an significant effect on all parameters observed. From this research giving best influence at dose OPEFBcompost100 g/10 kg medium + NPK 10 g/10 kg mediumon the increase of seedling height, leaf number, root volume, dry weight of seedlings and shoot roots ratioon oil palm seedlings which aged 6 months in Ultisol medium. Keyword: Oil palm empty fruit bunches(OPEFB) compost, NPK fertilizer,Ultisol medium